2017
DOI: 10.1002/anie.201706719
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Enantioselective Conjunctive Cross‐Coupling of 9‐BBN Borates

Abstract: Catalytic enantioselective conjunctive cross-coupling between 9-BBN borate complexes and aryl electrophiles can be accomplished with Ni salts in the presence of a chiral diamine ligand. The reactions furnish chiral 9-BBN derivatives in an enantioselective fashion and these are converted to chiral alcohols and amines, or engaged in other stereospecific C-C bond forming reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 65 publications
(11 reference statements)
0
20
0
3
Order By: Relevance
“…[1] To this end, recent efforts in our laboratory have led to the development of acatalytic conjunctive crosscoupling reaction (Scheme 1a). [3] Ac urrent limitation to the broad use of C(sp 3 )e lectrophiles in conjunctive couplings is that they only operate with aryl migrating groups.A dditionally,h ighly hindered tertiary electrophiles could not be engaged successfully in these reactions.I nt his report, we address these shortcomings through an alternate process that involves at ransition-metal/radical hybrid reaction, and show that these reactions can be accomplished in an enantioselective and catalytic fashion. [3] Ac urrent limitation to the broad use of C(sp 3 )e lectrophiles in conjunctive couplings is that they only operate with aryl migrating groups.A dditionally,h ighly hindered tertiary electrophiles could not be engaged successfully in these reactions.I nt his report, we address these shortcomings through an alternate process that involves at ransition-metal/radical hybrid reaction, and show that these reactions can be accomplished in an enantioselective and catalytic fashion.…”
mentioning
confidence: 99%
“…[1] To this end, recent efforts in our laboratory have led to the development of acatalytic conjunctive crosscoupling reaction (Scheme 1a). [3] Ac urrent limitation to the broad use of C(sp 3 )e lectrophiles in conjunctive couplings is that they only operate with aryl migrating groups.A dditionally,h ighly hindered tertiary electrophiles could not be engaged successfully in these reactions.I nt his report, we address these shortcomings through an alternate process that involves at ransition-metal/radical hybrid reaction, and show that these reactions can be accomplished in an enantioselective and catalytic fashion. [3] Ac urrent limitation to the broad use of C(sp 3 )e lectrophiles in conjunctive couplings is that they only operate with aryl migrating groups.A dditionally,h ighly hindered tertiary electrophiles could not be engaged successfully in these reactions.I nt his report, we address these shortcomings through an alternate process that involves at ransition-metal/radical hybrid reaction, and show that these reactions can be accomplished in an enantioselective and catalytic fashion.…”
mentioning
confidence: 99%
“…Die Ausbeuten waren in der Regel hoch und die Enantioselektivitäten moderat bis gut. Ein oxidativer Abbau von 3ag zu (S)-1,5-Diphenylpentan-2-ol [17] erlaubte die chemische Korrelation der Absolutkonfiguration; 3ag wurde S-Konfiguration zugeordnet. Das gewünschte Produkt wurde nicht erhalten, wenn ein sekundäres anstelle der obigen primären Alkylzinkbromide eingesetzt wurde (Cyclopentylzinkbromid wurde verwendet;s iehe Schema S3).…”
Section: Angewandte Chemieunclassified
“…[a] Nr.N ickel(II)-Salz Lçsungsmittel L Ausbeute [%] [b] e.r. Ein oxidativer Abbau von 3ag zu (S)-1,5-Diphenylpentan-2-ol [17] erlaubte die chemische Korrelation der Absolutkonfiguration; 3ag wurde S-Konfiguration zugeordnet. Die funktionellen Gruppen umfassen ein anderes Acetal (2b), Ether (2c und 2d), einen Ester (2e)u nd die Cyanogruppe (2f).…”
unclassified
“…Vinylboronicestersandtheirboronatecomplexesarehighly valuable substrates for CÀCb ond formation in the Suzuki-Miyaura coupling. [1] Moreover,v inyl boron ate complexes undergo 1,2-migration promoted by electrophilic halogenation [2] or by electrophilic palladation in conjunctive cross couplings,a sr ecently shown by Morken et al [3] Our laboratory and the group of Aggarwal independently demonstrated that in situ generated vinyl boron ate complexes II are efficient radical acceptors and that the corresponding radical anions III undergo ar adical polar crossover reaction, inducing a1 ,2-migration to provide secondary and tertiary alkyl boronic esters IV (Scheme 1). [4] Aggarwal et al further demonstrated that boron ate complexes of enantioenriched alkylboronic esters and furan-2-yllithium undergo stereospecific 1,2-metalate rearrangements in the reaction with the trifluoromethyl radical.…”
mentioning
confidence: 99%